2003
DOI: 10.1177/107602960300900406
|View full text |Cite
|
Sign up to set email alerts
|

P-selectin and Platelet-Derived Microparticles Associated with Monocyte Activation Markers in Patients with Pulmonary Embolism

Abstract: Platelet activation markers (platelet-derived microparticles and P-selectin on activated platelets), chemokines (monocyte chemotactic peptide and regulated on activation normally T-cell expressed and secreted), and soluble markers (sP-selectin, sE-selectin, sVCAM-1, and sCD14) were measured and compared in patients with pulmonary embolism (PE). These substances are thought to participate in the pathogenesis of PE. Levels of all of the platelet activation markers, chemokines, and soluble markers were higher in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 30 publications
0
21
0
1
Order By: Relevance
“…35,[46][47] In addition, platelets and PMPs are known to modulate the activity of the cells with which they interact, including monocytes, neutrophils, and endothelial cells. 27,29,35,46,49,50 For example, PMPs are important for platelet-derived CD154 to stimulate the maturation of monocyte-derived dendritic cells. 14 Because circulating PMPs and CD154 increase during inflammation, understanding the role of PMPs in the delivery of CD154 signals and the impact of this delivery on damage has broad implications.…”
Section: Discussionmentioning
confidence: 99%
“…35,[46][47] In addition, platelets and PMPs are known to modulate the activity of the cells with which they interact, including monocytes, neutrophils, and endothelial cells. 27,29,35,46,49,50 For example, PMPs are important for platelet-derived CD154 to stimulate the maturation of monocyte-derived dendritic cells. 14 Because circulating PMPs and CD154 increase during inflammation, understanding the role of PMPs in the delivery of CD154 signals and the impact of this delivery on damage has broad implications.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown platelet reactivity in patients with PE and DVT [7][8][9][10][11][12]. Mean platelet volume (MPV) is a measure of average platelet size [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…39 Elevated EMP levels were found in VTE patients, 40 and platelet-derived microparticle (PMP) levels were increased in PE patients. 41 In another study, it was shown that circulating procoagulant microparticles (CPMPs) and PMPs were significantly elevated in patients with acute PE, compared with those in controls lacking cardiovascular risk factors. However, when CPMP and PMP levels were compared with those of controls who had cardiovascular risk factors, there were no significant differences, emphasizing that the presence of cardiovascular risk factors must be adjusted in conditions with elevated MP levels.…”
Section: Microparticles (Mps) and Thrombosismentioning
confidence: 99%